Analysis of a Tall Structure Considering Mivan Technology Under Lateral Load Using ETABS - A Review - Jatin Kushwaha; Pradeep Kumar Nirmal; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2022)
High rise structures are prepared to resist seismic loads besides such massive stcutures are even subjected to wind load due to the magnitude and nature of wind load, hence such load factors are determined to understand its behaviour. This research is primarily focused to understand the behaviour of the wind response on high rise structures considering a G+15 structure. Mivan structure was analyzed in the study considering slab wall system instead of moment resisting fame for the structure. This study focuses on the level anomalies by considering various shapes in the arrangement of the building. In this paper presenting review of literatures related to analysis of tall structures